EMERGENCY NEUROSURGICAL CARE MANAGEMENT IN VORONEZH REGION - Yu. V. Struk; I. N. Banin; I. I. Vorobyev; K. Yu. Kudryashov; A. P. Tkachev; O. A. Yakusheva (Неотложная медицинская помощь, 2016)
BACKGROUND. Сraniocerebral injury is the most common type of trauma in Russian Federation especially among working age persons. These patients require unification of surgical tactics, intensive care and continuity of treatment in order to increase of effectiveness of treatment. Purpose of the study is evaluation of emergency neurosurgical aid efficiency in Voronezh region in terms of introduction of threelevel health care system.MATERIAL AND METHODS. Neurosurgical service functioning of Voronezh Clinical Center for Disaster Medicine has been evaluated. It included treatment and transportation of patients with a brain injury during 2012–2014.CONCLUSION. Admittance of patients with severe craniocerebral injury at the hospital with neurovisualization and telecommunication equipment improves neurosurgical aid efficiency of the Center for Disaster Medicine. It is possible due to effective patient’s data transmission and shortening of time before surgical intervention. The decrease of number of groundless neurosurgical team’s rides has been registered.